Pengembangan Usaha Kelompok Bina Usaha Ekonomi Keluarga Aisyiyah (BUEKA) PDA Sukoharjo Melalui Pemasaran Digital Berbasis Internet - Joko Suwandi; Surya Jatmika; Ahmad Chamsudin; Faizal Makhrus (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
The Covid-19 pandemic has been able to change consumer behavior in shopping. From those who have to go directly to traders to market stalls, shops or stalls, now with the help of sophisticated high-tech internet-based equipment, they can choose products through digital tracking facilities, transact and make payments through online applications and e-payments. This change was addressed by the UMS PKM team together with the Sukoharjo PDA Economic and Employment Council as partners to empower the businesses of Aisyiyah women assisted by BUEKA to change service strategies according to consumer demands. The programs carried out include; increasing human resources in carrying out marketing strategies for business products in the digital era, digitizing marketing and product placement on the Shopee and Facebook Marketplaces. The PKM program was successful; 1) Increase the insight of BUEKA fostered business actors about the demands of modern marketing and the interest in implementing them in their business development; 2) As many as 46% of BUEKA fostered businesses have been able to create digital advertisements and place their products on the Shopee marketplace and display them on Youtube; and 3) Increase sales volume by 20%.Pandemi Covid-19 telah mampu mengubah perilaku konsumen dalam berbelanja. Dari yang harus mendatangi pedagang langsung ke lapak pasar, toko atau warung, sekarang dengan bantuan kecanggihan peralatan berteknologi tinggi berbasis internet bisa memilih produk lewat fasilitas lacak digital, bertransaksi dan melakukan pembayaran melalui aplikasi online dan e-payment.  Perubahan ini disikapi oleh tim PKM UMS bersama Majelis Ekonomi dan Ketenagakerjaan PDA Sukoharjo sebagai mitra untuk memberdayakan usaha ibu-ibu Aisyiyah binaan BUEKA untuk merubah strategi layanan sesuai tuntutan konsumen. Program yang dilakukan meliputi; peningkatan SDM dalam melakukan strategi pemasaran produk usaha di era digital, digitalisasi pemasaran dan penempatan produk di Marketplace Shopee dan Facebook. Program PKM ini berhasil; 1) Meningkatkan wawasan pelaku usaha binaan BUEKA tentang tuntutan pemasaran modern dan minat untuk menerapkan dalam pengembangan usahanya; 2) Sebanyak 46% pelaku usaha binaan BUEKA telah mampu membuat iklan digital dan menempatkan produknya di marketplace Shopee dan menampilkan di Youtube; dan 3) Meningkatkan volume penjualan sebesar 20%.